Molecular analysis of rpoB gene mutations in rifampicin resistant Mycobacterium tuberculosis isolates by multiple allele specific polymerase chain reaction in Puducherry, South India - Ravibalan Thirumurugan; Maruthai Kathirvel; Kommoju Vallayyachari; Kesavan Surendar; Antony V. Samrot; Muthuraj Muthaiah (Elsevier, 2015)
Summary: Background: rpoB gene mutations in Mycobacterium tuberculosis (MTB) make the bacteria resistant to rifampicin. Thus, these mutations are surrogate markers for multi-drug resistance (MDR). The objective of this study was to evaluate an allele-specific multiplex-polymerase chain reaction (MAS-PCR) assay to detect mutations at codons 516, 526 and 531 of the rpoB gene. Methods: In total, 127 M. tuberculosis clinical isolates were subjected to standard drug susceptibility tests. A MAS-PCR assay was then performed to detect mutations in the rpoB gene. Three different allele-specific PCR assays were performed (single-step MAS-PCR) and the amplified products were sequenced. Results: Of the 127 isolates, 69 (54.3%) were multidrug resistant M. tuberculosis (MDR-TB), 21 (16.5%) were rifampicin mono-resistant and 37 (29.1%) were drug susceptible. The frequency of mutations at codons 531, 526 and 516 was 54.4%, 18.9% and 5.6%, respectively. A triple mutation was found in 4 (4.4%) isolates. Mutations in regions other than the 81-bp region were observed at codons 413 (11.1%), 511 (12.2%) and 521 (15.6%) of the rpoB gene. Conclusions: The simplicity and specificity of the MAS-PCR assay allows for easy implementation in clinical laboratories to detect rifampicin drug resistance in MDR-TB strains. Keywords: Mycobacterium tuberculosis, Rifampicin, Multiple allele-specific PCR, Drug resistance, rpoB gene